Trabeculectomy and EX-PRESS Implantation in Open-Angle Glaucoma: An Updated Meta-Analysis of Randomized Controlled Trials - Yi Sun; Bowen Zhang; Rouxi Zhou; Tao Wang; Juan Deng (Journal of Ophthalmology)
Purpose. Accumulating studies comparing the efficacy and safety of trabeculectomy and EX-PRESS implantation in open-angle glaucoma (OAG) report inconsistent findings. Thus, we conducted the updated meta-analysis to clarify the issue. Methods. Randomized controlled trials (RCTs) were selected through search of databases PubMed, Web of Science, Embase, and the Cochrane Library from their inception up until November 2018. The pooled mean difference (MD) for intraocular pressure reduction (IOPR) and antiglaucoma medication reduction, odds ratio (OR) for operative success, complication, and postoperative intervention was calculated using the random effects model. Results. 8 RCTs were enrolled, including 223 eyes in the EX-PRESS group and 217 eyes in the trabeculectomy group. EX-PRESS device implantation had a better IOPR% at 12 months postoperatively (MD = 8.9, 95% confidence interval (CI) = 2.5–15.3, P=0.006). There was no statistically significant difference in the antiglaucoma medication reduction (MD = 6.01, 95% CI = −4.13–16.15, P=0.25) and qualified success (P>0.05). Statistically higher complete success at 1 year postoperatively was found in the EX-PRESS group (OR = 3.26, 95% CI = 1.24–8.55, P=0.02). EX-PRESS was associated with a lower frequency of increased IOP (OR = 0.15, 95% CI = 0.03–0.93, P=0.04) and hyphema (OR = 0.20, 95% CI = 0.05–0.74, P=0.02). Less postoperative intervention was needed in the EX-PRESS group (OR = 0.43, 95% CI = 0.20–0.94, P=0.04). Conclusion. For OAG patients, EX-PRESS implantation provided better efficacy in IOP control and complete success at 1 year postoperatively, with fewer increased IOP and hyphema as well as postoperative interventions. EX-PRESS device and trabeculectomy were similar in the qualified success and antiglaucoma medication reduction.